Carbon geosequestration in limestone: Pore-scale dissolution and geomechanical weakening. (November 2017) - Lebedev, Maxim; Zhang, Yihuai; Sarmadivaleh, Mohammad; Barifcani, Ahmed; Al-Khdheeawi, Emad; Iglauer, Stefan
Highlights: Two resolutions apply on the microCT in-situ scanning. Heterogeneous matrix dissolution observed in high resolution. Dynamic Damköhler number quantified with length. Rock matrix weakening induced by CO2 - saturated brine flooding. Abstract: Carbon dioxide geosequestration in deep saline aquifers or oil and gas reservoirs is a key technology to mitigate anthropogenic greenhouse gas emissions. Porous carbonate rock is a potential host rock for CO2 storage; however, carbonate rock chemically reacts when exposed to the acidic brine (which is created by the addition of CO2, CO2 -saturated brine). These reactive transport processes are only poorly understood, particularly at the micrometre scale, and importantly how this affects the geomechanical rock properties. We thus imaged a heterogeneous oolitic limestone (Savonnières limestone) core before and after flooding with brine and CO2 -saturated brine at representative reservoir conditions (323 K temperature, 10 MPa pore pressure, 5 MPa effective stress) in-situ at high resolutions (3.43 μm and 1.25 μm voxel size) in 3D with an x-ray micro-computed tomograph; and measured the changes in nano-scale mechanical properties induced by acid exposure. Indeed the carbonate rock matrix partially dissolved, and absolute and effective porosity and permeability significantly increased. This dissolution was confined to the original flow channels and inlet points. Importantly, the rock matrix weakened significantly (- 47% in indentation modulus) due to the acid exposure.